Positive behavior management in physical activity settings - Lavay, Barry Wayne; French, Ronald W. 1942-; Henderson, Hester (Human Kinetics, 2016)
It's never been more challenging to manage behavior and motivate students in a physical activity setting. There are more at-risk children and students with disabilities to manage. Physical activity professionals also face the unique challenge of providing instruction to large groups with limited resources and distractions galore. If not handled correctly, these challenges can quickly add up to chaos, ineffective instruction, and frustrated, burnt-out physical activity professionals. That's where the third edition of Positive Behavior Management in Physical Activity Settings, Third Edition comes in. This resource will help you not only overcome those and other discipline challenges, but also use tried-and-true, positive techniques to develop appropriate and responsible behaviors and good character among all learners. This new edition incorporates principles, methods, and instructional practices from psychology, special education, pedagogy, recreation, athletics, and coaching. It shows teachers, coaches, and recreation leaders how to apply the principles that have proven effective in schools, youth sport programs, and recreation sites. -- Publisher's website